Optimalisasi Limbah Organik menjadi Pupuk Cair di Gampong Pasie Aceh Baro - Evi Julianita Harahap; Kasmawati Kasmawati; Rahmah Husna Yana; Nhyra Kamala Putri; Suci Eka Putri (Jurnal Pengabdian Masyarakat (ABDIRA), 2026)
Household organic waste in Gampong Pasie Aceh Baro has not been optimally utilized, potentially increasing the environmental burden and community dependence on chemical fertilizers. This community service initiative focuses on enhancing the knowledge and skills of the Women Farmers Group, "Wanita Berusaha," in processing local materials into liquid organic fertilizer (LOF) to support sustainable agricultural practices. The method employed involved socialization, including material presentation, hands-on fertilizer production, fermentation monitoring, and outcome evaluation, involving 22 participants. The evaluation showed a 100% improvement in soft skills, including knowledge of the materials and procedures for LOF production, active participation in the activities, and environmental awareness that supports sustainable agricultural practices. Furthermore, there is a potential for increased economic value through reduced expenditure on chemical fertilizers and the utilization of household waste. This activity underscores the importance of rural community empowerment in managing local resources as a fundamental step toward sustainable agriculture.